2019
DOI: 10.1049/iet-stg.2019.0002
|View full text |Cite
|
Sign up to set email alerts
|

Case study on the effects of partial solar eclipse on distributed PV systems and management areas

Abstract: Photovoltaic (PV) systems depend on irradiance, ambient temperature and module temperature. A solar eclipse causes significant changes in these parameters, thereby impacting PV generation profile, performance, and power quality of larger grid where they connect to. This paper presents a case study to evaluate the impacts of the solar eclipse of August 21, 2017 on two real-world grid-tied PV systems (1.4MW and 355kW) in Miami and Daytona, Florida, the feeders they are connected to, and the management areas they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…Processing (PRC): Five levels of processing exist: descriptive (statistics, exploratory visualisation, and regression between dependent and independent variables to understand events [25]), diagnostic (root-cause and correlation studies to understand why the observed events have occurred) [26,27], predictive (supervised, semi-supervised, and unsupervised regression and classification models to determine, based on the understanding from past and current events, including seasonal trends, how they will likely progress in the short-term or long-term future [28][29][30]), prescriptive (optimisation and numerical analysis to come up with robust sets of feasible actions for optimised outcomes that maximise an objective [31]), and cognitive (deep learning and decision-making to refine feasible decisions that encode human thought process, experiences, and available context to form actionable decisions [32,33]).…”
Section: Big Data Lifecycle Stagesmentioning
confidence: 99%
“…Processing (PRC): Five levels of processing exist: descriptive (statistics, exploratory visualisation, and regression between dependent and independent variables to understand events [25]), diagnostic (root-cause and correlation studies to understand why the observed events have occurred) [26,27], predictive (supervised, semi-supervised, and unsupervised regression and classification models to determine, based on the understanding from past and current events, including seasonal trends, how they will likely progress in the short-term or long-term future [28][29][30]), prescriptive (optimisation and numerical analysis to come up with robust sets of feasible actions for optimised outcomes that maximise an objective [31]), and cognitive (deep learning and decision-making to refine feasible decisions that encode human thought process, experiences, and available context to form actionable decisions [32,33]).…”
Section: Big Data Lifecycle Stagesmentioning
confidence: 99%
“…Many metrics are currently used to evaluate PV system performance [60][61][62]. While uncorrected PR, measured using (11), is widely used by the utilities to measure the performance of a particular PV system, it is highly dependent on local weather (especially module temperature) and hence varies significantly over the course of a year [63]. Therefore, PR is not an effective metric to compare performance of two PV systems that experience different weather conditions.…”
Section: Metrics To Evaluate Pv Performancementioning
confidence: 99%
“…For the below series of equations, consider kWhAC actual to denote the observed energy (in AC side) generated by the PV system, P DC to denote the nameplate rated generation capacity (DC side) of the PV system, and kWh sun to denote the amount of solar energy received by the PV system cumulatively across its entire area. Then, the uncorrected PR is calculated by [64] PR = kWhAC actual /P DC kWh sun /1000 (11) This work also considers yield (PV systems of different sizes are not directly comparable), and PR corrected to STC (PV systems employing different PV models are not directly comparable), and capacity factor (ratio of the observed PV generation over a time period to its potential generation if it functioned at its full nameplate capacity continuously over the same time period). Given a time instance t in N total number of time instances and the observed generation (in kW) from the PV system at the time t denoted by kWAC actual (t), the yield, PR corrected to STC, and capacity factor are calculated as follows [65]:…”
Section: Metrics To Evaluate Pv Performancementioning
confidence: 99%
“…For environmental reasons, there has been a consistent increase in global installation of photovoltaic (PV) systems. This is further facilitated by the declining cost of PV modules over the years [1][2][3][4][5]. The increase is PV installations is evident as the financial investments in PV installation globally is also on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…The increase is PV installations is evident as the financial investments in PV installation globally is also on the rise. The increase in levels of PV penetration have lead to several challenges which include reverse power flow, voltage control issues, power quality issues [6][7][8][9] (voltage and current harmonics, flicker, momentaries), protection coordination problems, and possible increase in system losses. [3,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%